Narrative Therapy and the Nature Of “Innovative Moments” in the Construction of Change - Gonçalves, Miguel M. (2009)
According to the narrative metaphor of psychotherapy, clients transform themselves by changing their life stories. According to the narrative therapy of White and Epston (1990), the construction of change occurs from the expansion of unique outcomes, or innovative moments as we prefer to call them, that is, the development of episodes outside the problem-saturated narrative. Unique outcomes operate as exceptions to the rule (i.e., to the problem-saturated story) that can be changed to a new rule (i.e., a new narrative). We suggest that some forms of unique outcomes can operate as shadow-voices (Gustafson, 1992) of the problem-saturated story, allowing a temporary release from the problem, but facilitating a return to it. In our view, there is a particular type of unique outcome —re-conceptualization— that facilitates sustained change. This kind of innovation facilitates the emergence of a meta-level perspective about the change process itself, and in turn, enables the active positioning of the person as an author of the new narrative.